(untitled) (Veterinary Science, 2019)
The objective of the present study was to evaluate the variation of the live weight of Creole goats males studied within the Castron Plan at the beginning and at the end of the service period, in the South of Mendoza. For that purpose, 824 Creole type males, divided according to age by dental chronology, were used. Live weight was evaluated with an electronic scale of 150 kg maximum capacity, with 50g of precision, in May (austral autumn), at the beginning of the reproductive stage and in September (austral spring), at the time that the goats were removed from the producing establishments by “the castronero”. The experimental design responded to a completely randomized model, evaluating standard means and deviations between the different work moments by Tukey test applying the statistical program InfoStat 2.0. The results showed 28.13 weights±4.4 and 27.94±5.1 kg for males with 2 teeth, in September, and autumn respectively; 52.35 ± 4.7 and 41, 92±7,4 kg for males with 4 teeth, males 68.4 ± 6.3 and 56.7 ±6 , 7 kg for the goats with 6 teeth, 78,84 ± 6.2 and 62, 3±7, 6 kg for males with full mouth and 70.4 ±6, 9 and 57.4 ±7 , 3 kg for the goats with half tooth, there is a significant statistical difference (p≤0. 05) between the two periods evaluated for animals 4-6 teeth, mouth full and half tooth. We conclude showing the live weight of the selected Creole goats in Plan Castron a significant seasonal variation between the onset of the reproductive season (austral autumn) and the end of the service stage (austral spring) influenced by the condition of the natural grassland for every moment and the males´ activity during the reproductive season